Analysis of Malay-language scholarly books distribution from the perspectives of the publisher - Mohd Asri, Nurul Fadzlin; Sha’ri, Sharil Nizam; Kamaruddin, Rohaidah; Hamzah, Zaitul Azma Zainon; Che Rodi, Rozita (Human Resource Management Academic Research Society, 2021)
The continuation of publication of scholarly books in Malay language should be maintained as a medium of knowledge dissemination through a written language that can be read by the people of this country. But, the Malay-language scholarly books has received poor reception among the target group. This is so because, the society underestimate the quality of the Malay language in interpreting the diverse disciplines of science. This phenomenon has affected the landscape of Malay-language scholarly book publishing industry in Malaysia. Nevertheless, there are, Malay-language scholarly books that gain recognition, both locally and internationally. This clearly proves that the quality of the book in the publishing process is one of the strategies adopted in promoting the book. Thus, this study aims to identify the Malay-language scholarly books published by Universiti Putra Malaysia (UPM Press) and analyze the distribution practices of the selected Malay-language scholarly books by using the principles of marketing by Kotler & Armstrong (2019). The findings of this study prove that, UPM Press has practiced the principles of marketing as a strategy to distribute their scholarly books since the scholarly books published by the UPM Press do have its own place in the market of Malaysian book industry.